Gender Pay Gaps across STEM Fields of Study - Tomasz Zając; Iga Magda; M. Bożykowski; Agnieszka Chłoń-Domińczak; M. Jasiński (Institute of Labor Economics (IZA), 2023)
Gender pay gaps in earnings are well-documented in the literature. However, new factors contributing to women's lower earnings have emerged and remain under-researched. Educational choices are among them. We use a rich administrative dataset from Poland, a Central Eastern European country with high tertiary education enrolment and high female employment rates among young women, to study gender pay gaps among tertiary education graduates with degrees in different fields of study while paying particular attention to STEM fields graduates (science, technology, engineering, and mathematics). We find that already in the first year after graduation, women earn over 20% less than men. This gap widens over time. We also find significant variation across different STEM fields both in the size of the gender pay gap and in how it changes over time. The gap is largest among mathematics graduates, at over 25%; while it does not exceed 3% among chemical and Earth sciences graduates. As these differences narrow only slightly within the first four years of graduates' working careers, policymakers' efforts to increase the number of women earning STEM degrees may not be enough to achieve gender pay equality.
Keywords: J16; J24; J3; J71; 330; STEM; labor market; higher education; gender pay gap; field of study; Poland